2018
DOI: 10.1021/acs.analchem.7b05331
|View full text |Cite
|
Sign up to set email alerts
|

A New Lysosome-Targetable Turn-On Fluorogenic Probe for Carbon Monoxide Imaging in Living Cells

Abstract: A lysosome-targetable fluorogenic probe, LysoFP-NO, was designed and synthesized based on a naphthalimide fluorophore that can detect selectively carbon monoxide (CO) in HEPES buffer (pH 7.4, 37 °C) through the transformation of the nitro group into an amino-functionalized system in the presence of CO. LysoFP-NO triggered a "turn-on" fluorescence response to CO with a simultaneous increase of fluorescence intensity by more than 75 times. The response is selective over a variety of relevant reactive nitrogen, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 44 publications
3
63
0
Order By: Relevance
“…The heavy transition metal free reduction of nitro to amine functional group is devoid of any risk of side effect like carcinogenesis. [28] Very recently, a nuclear targetable probe NucFP-NO 2 for detecting CO inside the nucleus is also reported by our group obeying similar mechanism of action of reducing nitro/amine functionality in the presence of CO. The nucleus is enriched of DNA and is the most vital organelle of eukaryotic cells.…”
Section: Fluorescent Probes For Lysosomal and Nuclear-targetable Co Dmentioning
confidence: 54%
See 1 more Smart Citation
“…The heavy transition metal free reduction of nitro to amine functional group is devoid of any risk of side effect like carcinogenesis. [28] Very recently, a nuclear targetable probe NucFP-NO 2 for detecting CO inside the nucleus is also reported by our group obeying similar mechanism of action of reducing nitro/amine functionality in the presence of CO. The nucleus is enriched of DNA and is the most vital organelle of eukaryotic cells.…”
Section: Fluorescent Probes For Lysosomal and Nuclear-targetable Co Dmentioning
confidence: 54%
“…Lastly, the widely accepted mechanism involved in this field is the reaction based reduction of aryl nitro group to aryl amino derivative of the organic probe in the presence of CORM without using any heavy metals. Due to the conversion of electron withdrawing aryl nitro group to electron releasing aryl amino group, turn on fluorescence occurs and the process is non‐toxic as well as having nominal cost . Beside this a lanthanide based system showing turn‐on fluorescence in the presence of CORM‐3, spirolactam ring opening in the presence of CORM‐3 resulting turn‐on fluorescence, is also reported recently and the mechanistic discussion of these reports are depicted on the respective sections.…”
Section: Introductionmentioning
confidence: 69%
“…In 2017, Dhara et al reported a lysosome-targeting uorescent probe 51 for the detection of CO based on a new recognition site. 69 The probe consisted of the following three parts: 1,8naphthalimide (acted as an ideal uorophore), a morpholine unit (served as the lysosome-targeting moiety) and a nitro group (a novel CO-responsive site). Probe 51 exhibited very weak uorescence intensity (F ¼ 0.0016) due to the PET quenching effect of the nitro group on the 1,8-naphthalimide.…”
Section: Nitro Reductionmentioning
confidence: 99%
“…In the context of development of fluorescent sensors for selective detection and imaging of trace level ions/molecules and the assessment of the target species through fluorescence turn‐on sensors in solution or in solid state, several photophysical (like PET, CHEF, ICT, FRET etc) processes have been considered enormously . There are a huge number of chemosensors in solution state in the literature compared to luminescent materials in solid states.…”
Section: Introductionmentioning
confidence: 99%